Catalyst for producing hydrogen by electrolyzing water as well as preparation method and application of catalyst
Through the catalyst prepared by the solvent thermal reaction, the problem of poor stability of the catalyst in the existing technology and the complex and high cost of the alloy hydrogen hydride technology in the existing technologies, and achieve efficient and environmentally friendly electrolytic hydrogen -making effects.
Patent Information
- Application Number
- CN202411578681.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-07
AI Technical Summary
In the existing electrolytic hydrogen production technology, there are stability problems when using metal palladium as a catalyst, and the synthesis of alloy hydrides containing metal palladium is complicated, the raw material cost is high, and it is not environmentally friendly.
By mixing the alcohol decentralized liquid, metal front-wheel drive dispersing liquid, metal-diverted liquid dispersing liquid, and 1-alcohol solution of 1-phenol, the solvent heat reaction is performed to prepare the metal alloy hydrogen hydrogen catalyst. This method is simple, low in cost, environmentally friendly and non -toxic.
The electrocatalytic performance of hydrogen production by electrolysis of water is improved, the overpotential during the electrolysis process is reduced, the energy conversion efficiency is improved, and the process is simple and environmentally friendly.
Smart Images

Figure CN119352071A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water electrolysis hydrogen production, and in particular to a water electrolysis hydrogen production catalyst and a preparation method and application thereof. Background Art
[0002] As a low-carbon and efficient clean energy, hydrogen plays a key role in global energy transformation and addressing climate change. In particular, hydrogen produced by water electrolysis driven by renewable energy, namely green hydrogen, does not emit greenhouse gases during its production process and is therefore generally considered to be one of the key ways to achieve carbon neutrality. Since the efficiency and cost of hydrogen produced by water electrolysis depend largely on the catalyst used, efficient catalysts can significantly reduce the overpotential in the electrolysis process, thereby improving energy conversion efficiency and achieving efficient hydrogen production by water electrolysis.
[0003] Palladium metal has become an ideal choice to replace platinum due to its low cost, platinum-like catalytic activity, good stability and relative abundance of resources, especially in the field of hydrogen production by water electrolysis. However, due to the strong bonding force between palladium and hydrogen, hydrogen desorption is difficult, which makes it face stability problems during water electrolysis. Metal alloy hydrides prepared using palladium metal as a precursor can effectively improve the adsorption free energy of the catalyst, thereby optimizing the adsorption energy of the intermediate product and ultimately improving the performance of hydrogen production by water electrolysis. However, the synthesis of alloy hydrides containing palladium metal faces challenges such as complex operating procedures, high raw material costs, and the possibility that some raw materials may have adverse effects on the environment. Summary of the invention
[0004] The object of the present invention is to provide a water electrolysis hydrogen production catalyst and a preparation method and application thereof. The preparation method is simple to operate, low in cost, and environmentally friendly, and the prepared water electrolysis hydrogen production catalyst has high electrocatalytic performance.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a catalyst for producing hydrogen by electrolysis of water, comprising the following steps:
[0007] The ethanol-water dispersion of palladium, the metal precursor dispersion and the ethanol solution of 1-naphthol are mixed to perform a solvothermal reaction to obtain the water electrolysis hydrogen production catalyst;
[0008] The water electrolysis hydrogen production catalyst is an alloy hydride of metal palladium.
[0009] Preferably, the palladium in the ethanol-water dispersion of palladium is nano-palladium;
[0010] The microscopic morphology of the nano-palladium includes one or more of nanoparticles, nanowires, nanotubes, nanodendrites, nanoflowers, nanorods and nanostars;
[0011] The concentration of the palladium ethanol water dispersion is 50-200 mg / L.
[0012] Preferably, the metal precursor in the metal precursor dispersion includes one or more of ruthenium trichloride, cupric chloride dihydrate, ferric chloride hexahydrate, nickel chloride, zinc chloride and cobalt chloride hexahydrate;
[0013] The concentration of the metal precursor dispersion is 0.01-0.1 mol / L.
[0014] Preferably, the concentration of the 1-naphthol ethanol solution is 0.1 to 1 mol / L.
[0015] Preferably, the dosage ratio of palladium in the ethanol-water dispersion of palladium to the metal precursor dispersion is (1-10) mg: (0.01-1) mL.
[0016] Preferably, the volume ratio of the metal precursor dispersion liquid to the 1-naphthol ethanol solution is (0.01-1):(0.3-0.7).
[0017] Preferably, the temperature of the solvent thermal reaction is 100 to 240° C., and the time is 1 to 36 hours.
[0018] Preferably, after the solvothermal reaction is completed, centrifugal washing and drying are further performed in sequence.
[0019] The present invention also provides a water electrolysis hydrogen production catalyst prepared by the preparation method described in the above technical solution, wherein the water electrolysis hydrogen production catalyst is a metal alloy hydride;
[0020] The metal alloy hydride includes palladium crystals and dopant metal atoms and hydrogen atoms embedded in the palladium crystal structure.
[0021] The present invention also provides the use of the water electrolysis hydrogen production catalyst described in the above technical solution in the field of water electrolysis hydrogen production.
[0022] The present invention provides a method for preparing a catalyst for producing hydrogen by electrolysis of water, comprising the following steps: mixing an ethanol aqueous dispersion of palladium, a metal precursor dispersion and an ethanol solution of 1-naphthol, and performing a solvothermal reaction to obtain the catalyst for producing hydrogen by electrolysis of water; the catalyst for producing hydrogen by electrolysis of water is an alloy hydride of metal palladium. The present invention uses palladium as a substrate, and prepares a metal alloy hydride catalyst by doping metal elements through a one-step solvothermal reaction, thereby ensuring the effective introduction of metal atoms and hydrogen atoms, increasing the active sites on the palladium surface, expanding the electron transfer channel, and improving the electrochemical activity; at the same time, the preparation method for preparing the catalyst for producing hydrogen by electrolysis of water through a one-step solvothermal reaction is simple to operate, environmentally friendly and non-toxic, and has low raw material costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 TEM image and EDS image of the ruthenium-palladium alloy hydride described in Example 1;
[0024] Figure 2 The XPS graphs of the ruthenium-palladium alloy hydride described in Example 1 and the ruthenium-palladium alloy described in Comparative Example 1;
[0025] Figure 3 XRD patterns of the ruthenium-palladium alloy hydride described in Example 1, the ruthenium-palladium alloy described in Comparative Example 1, and the ruthenium hydride described in Comparative Example 2;
[0026] Figure 4 The linear sweep voltammetry (LSV) curves of the ruthenium-palladium alloy hydride of Example 1, the ruthenium-palladium alloy of Comparative Example 1, and the palladium hydride of Comparative Example 2 in the test of electrolyzing water to produce hydrogen are shown.
[0027] Figure 5 The linear sweep voltammetry (LSV) curves of the ruthenium-palladium alloy hydride described in Example 2, the ruthenium-palladium alloy hydride described in Example 3, the ruthenium-palladium alloy hydride described in Example 4, and the copper-palladium alloy hydride described in Example 5 during the water electrolysis hydrogen production test. DETAILED DESCRIPTION
[0028] The present invention provides a method for preparing a catalyst for producing hydrogen by electrolysis of water, comprising the following steps:
[0029] The ethanol-water dispersion of palladium, the metal precursor dispersion and the ethanol solution of 1-naphthol are mixed to perform a solvothermal reaction to obtain the water electrolysis hydrogen production catalyst;
[0030] The water electrolysis hydrogen production catalyst is an alloy hydride of metal palladium.
[0031] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0032] In the present invention, the palladium in the ethanol-water dispersion of palladium is preferably nano palladium; the microscopic morphology of the nano palladium preferably includes one or more of nanoparticles, nanowires, nanotubes, nanodendrites, nanoflowers, nanorods and nanostars; when the microscopic morphology of the nano palladium is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the nano palladium with the above specific microscopic morphology, and can be mixed in any ratio. In the present invention, the solvent in the ethanol-water dispersion of palladium is preferably ethanol aqueous solution; the concentration of ethanol in the ethanol aqueous solution is 50 vol%. In the present invention, the concentration of the ethanol-water dispersion of palladium is preferably 50-200 mg / L, more preferably 100-150 mg / L. In the present invention, the ethanol-water dispersion of palladium is preferably prepared by adding palladium to a solvent for dispersion; the present invention has no special restrictions on the dispersion process, and can be carried out using a process well known to those skilled in the art. In an embodiment of the present invention, the concentration of the ethanol-water dispersion of palladium can be 125 mg / L. The microscopic morphology of palladium in the ethanol-water dispersion of palladium is nano dendrites. In an embodiment of the present invention, the preparation method of palladium in the ethanol-water dispersion of palladium can be: add 0.5 mL of a 0.05 mol / L palladium acetate acetic acid solution to 3 mL of water, add 0.5 mL of a 0.5 mol / L 1-naphthol ethanol solution, react in a 60°C water bath for 2 hours, wash with ethanol by centrifugation 6 times, and freeze-dry for 24 hours to obtain palladium with a microscopic morphology of nanodendrites.
[0033] In the present invention, the metal precursor in the metal precursor dispersion preferably includes one or more of ruthenium trichloride, cupric chloride dihydrate, ferric chloride hexahydrate, nickel chloride, zinc chloride and cobalt chloride hexahydrate. When the metal precursor is two or more of the above specific selections, the present invention does not have any special restrictions on the ratio of the above specific substances. In the present invention, the solvent in the metal precursor dispersion is deionized water. In the present invention, the concentration of the metal precursor dispersion is preferably 0.01 to 0.1 mol / L, more preferably 0.03 to 0.06 mol / L. In an embodiment of the present invention, the concentration of the metal precursor dispersion may be 0.05 mol / L; the metal precursor in the metal precursor dispersion may be cupric chloride dihydrate, ruthenium trichloride, nickel chloride, ferric chloride hexahydrate, zinc chloride, and cobalt chloride hexahydrate.
[0034] In the present invention, the concentration of the 1-naphthol ethanol solution is preferably 0.1 to 1 mol / L, more preferably 0.3 to 0.7 mol / L. In an embodiment of the present invention, the concentration of the 1-naphthol ethanol solution may be 0.5 mol / L. In the present invention, the role of the 1-naphthol in the 1-naphthol ethanol solution is a reducing agent that reduces metal ions to metal elements.
[0035] In the present invention, the ratio of palladium to metal precursor dispersion in the ethanol-water dispersion of palladium is preferably (1-10) mg: (0.01-1) mL, more preferably (3-6) mg: (0.01-0.5) mL. In an embodiment of the present invention, the ratio of palladium to metal precursor dispersion in the ethanol-water dispersion of palladium is 4 mg: 0.1 mL, 4 mg: 0.01 mL or 4 mg: 0.4 mL.
[0036] In the present invention, the volume ratio of the metal precursor dispersion and the 1-naphthol ethanol solution is preferably (0.01-1): (0.3-0.7), more preferably (0.01-0.5): (0.4-0.6). In an embodiment of the present invention, the volume ratio of the metal precursor dispersion and the 1-naphthol ethanol solution can be 0.1:0.5, 0.01:0.5 or 0.4:0.5.
[0037] In the present invention, the mixture of the ethanol aqueous dispersion of palladium, the metal precursor dispersion and the ethanol solution of 1-naphthol is preferably prepared by sequentially adding the metal precursor dispersion and the ethanol solution of 1-naphthol to the ethanol aqueous dispersion of palladium. The present invention does not have any particular limitation on the manner of adding, and the manner well known to those skilled in the art can be used.
[0038] In the present invention, the temperature of the solvent thermal reaction is preferably 100-240°C, more preferably 150-200°C; the time is preferably 1-36h, more preferably 12-20h. In an embodiment of the present invention, the temperature of the solvent thermal reaction can be 100°C, 200°C or 240°C; the time can be 12h, 1h or 36h.
[0039] After the solvothermal reaction is completed, the present invention also preferably includes centrifugal washing and drying performed in sequence; the present invention does not have any special restrictions on the process of the centrifugal washing, and the process well known to those skilled in the art can be used. In the present invention, the washing is preferably washed with ethanol for 6 times. In the present invention, the drying method is preferably freeze-drying. The present invention does not have any special restrictions on the process of the freeze-drying, and the process well known to those skilled in the art can be used. In an embodiment of the present invention, the freeze-drying time can be 24h.
[0040] The present invention also provides a water electrolysis hydrogen production catalyst prepared by the preparation method described in the above technical solution, wherein the water electrolysis hydrogen production catalyst is a metal alloy hydride;
[0041] The metal alloy hydride includes palladium crystals and dopant metal atoms and hydrogen atoms embedded in the palladium crystal structure.
[0042] In an embodiment of the present invention, the molar ratio of the doping metal atoms to the palladium crystals may be 7:67.
[0043] In the present invention, the doping metal atoms preferably include one or more of ruthenium, copper, iron, nickel, zinc and cobalt. When the doping metal atoms are two or more of the above-mentioned specific selections, the present invention has no special limitation on the ratio of the above-mentioned specific doping metal atoms, and they can be mixed in any ratio.
[0044] The present invention also provides the use of the water electrolysis hydrogen production catalyst described in the above technical solution in the field of water electrolysis hydrogen production.
[0045] In the present invention, the application method preferably includes:
[0046] The present invention mixes the water electrolysis hydrogen production catalyst and the conductive carbon powder described in the above technical solution, and then adds isopropanol, deionized water and a Nafion solution with a mass concentration of 5% to obtain ink.
[0047] In the present invention, the mass ratio of the water electrolysis hydrogen production catalyst and the conductive carbon powder is preferably 1:1; the volume ratio of the isopropanol, deionized water and Nafion solution is preferably 6:3:1. In the present invention, the concentration of the water electrolysis hydrogen production catalyst in the ink is preferably 1-5 g / L, more preferably 2 g / L.
[0048] After obtaining the ink, the present invention drops the ink onto a glassy carbon electrode and then performs electrolysis in a potassium hydroxide solution.
[0049] In the present invention, the dripping amount is preferably 8 to 15 μL, more preferably 9 to 10 μL.
[0050] In the present invention, the concentration of the potassium hydroxide solution is preferably 1 mol / L.
[0051] In the present invention, electrochemical measurements were all performed in a standard three-electrode electrochemical cell at room temperature using a CHI 660E workstation (CH Instruments, Shanghai Chenhua Co., Ltd.). A graphite rod was used as an auxiliary electrode and a saturated calomel electrode (SCE) was used as a reference electrode. A glassy carbon electrode (3 mm in diameter) loaded with a catalyst ink for hydrogen production by electrolysis of water was used as a working electrode. The hydrogen evolution reaction (HER) by electrolysis of water was studied in a 1.0 M KOH solution saturated with N2 at a scan rate of 5 mV / s. All electrode potentials were referenced to a reversible hydrogen electrode (RHE). In our electrochemical test system, in 1.0 M KOH, E(RHE) = E(SCE) + 1.068 V.
[0052] The water electrolysis hydrogen production catalyst provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0053] Example 1
[0054] 0.5 mL of 0.05 mol / L palladium acetate was added to 3 mL of water, and then 0.5 mL of 0.5 mol / L 1-naphthol ethanol solution was added, and the mixture was reacted in a water bath at 60°C for 2 h. After the reaction was completed, the mixture was washed by centrifugation with ethanol for 6 times, and freeze-dried for 24 h to obtain metal palladium nanodendrites.
[0055] 4 mg of metal palladium nanodendrites were added to 32 mL of ethanol aqueous solution with a volume percentage of 50% ethanol for dispersion, and then 0.1 mL of 0.05 mol / L ruthenium trichloride solution and 0.5 mL of 0.5 mol / L 1-naphthol ethanol solution were added. After solvothermal reaction at 200° C. for 12 h, the mixture was centrifuged and washed with ethanol for 6 times, and freeze-dried for 24 h to obtain ruthenium-palladium alloy hydride (the molar ratio of ruthenium to palladium was 7:67, and the molar ratio of hydrogen to palladium was 3:7);
[0056] Since the ratio of each element in the sample obtained from the experiment is different from the feed ratio, it is necessary to determine it according to the actual sample. The element ratio of the sample is only provided in Example 1 and will not be provided later.
[0057] The ruthenium-palladium alloy hydride was subjected to TEM and EDS tests, and the test results are as follows: Figure 1 As shown, (a, b) are EDS images of ruthenium-palladium alloy hydride, (c) is a TEM image of ruthenium-palladium alloy hydride, and (d) is a TEM image of palladium nanodendrites; Figure 1 It can be seen that the morphology of the ruthenium-palladium alloy hydride is nanodendrites, and EDS testing can observe that the atomic ratio of ruthenium atoms to palladium atoms in the ruthenium-palladium alloy hydride is 1:9.
[0058] Example 2
[0059] Metal palladium nanodendrites were prepared by referring to Example 1;
[0060] 4 mg of metal palladium nanodendrites were added to 32 mL of ethanol aqueous solution with a volume percentage of 50% ethanol for dispersion, and then 0.01 mL of 0.05 mol / L ruthenium trichloride solution and 0.5 mL of 0.5 mol / L 1-naphthol ethanol solution were added. After solvothermal reaction at 200°C for 12 hours, the mixture was washed by centrifugation with ethanol for 6 times and freeze-dried for 24 hours to obtain ruthenium-palladium alloy hydride.
[0061] Example 3
[0062] Metal palladium nanodendrites were prepared by referring to Example 1;
[0063] 4 mg of metal palladium nanodendrites were added to 32 mL of ethanol aqueous solution with a volume percentage of 50% ethanol for dispersion, and then 0.4 mL of 0.05 mol / L ruthenium trichloride solution and 0.5 mL of 0.5 mol / L 1-naphthol ethanol solution were added. After solvothermal reaction at 200°C for 12 hours, the mixture was washed by centrifugation with ethanol for 6 times and freeze-dried for 24 hours to obtain ruthenium-palladium alloy hydride.
[0064] Example 4
[0065] Metal palladium nanodendrites were prepared by referring to Example 1;
[0066] 4 mg of metal palladium nanodendrites were added to 32 mL of 50% ethanol by volume ethanol aqueous solution for dispersion, and then 0.1 mL of 0.05 mol / L ruthenium trichloride solution and 0.5 mL of 0.5 mol / L 1-naphthol ethanol solution were added. After solvothermal reaction at 240°C for 12 hours, the mixture was washed by centrifugation with ethanol for 6 times and freeze-dried for 24 hours to obtain ruthenium palladium alloy hydride.
[0067] Example 5
[0068] Metal palladium nanodendrites were prepared by referring to Example 1;
[0069] 4 mg of metal palladium nanodendrites were added to 32 mL of ethanol aqueous solution with a volume percentage of 50% ethanol for dispersion, and then 0.1 mL of 0.05 mol / L ruthenium trichloride solution and 0.5 mL of 0.5 mol / L 1-naphthol ethanol solution were added. After solvothermal reaction at 200°C for 1 hour, the mixture was washed by centrifugation with ethanol for 6 times and freeze-dried for 24 hours to obtain ruthenium-palladium alloy hydride.
[0070] Example 6
[0071] Metal palladium nanodendrites were prepared by referring to Example 1;
[0072] 4 mg of metal palladium nanodendrites were added to 32 mL of ethanol aqueous solution with a volume percentage of 50% ethanol for dispersion, and then 0.1 mL of 0.05 mol / L ruthenium trichloride solution and 0.5 mL of 0.5 mol / L 1-naphthol ethanol solution were added. After solvothermal reaction at 200°C for 36 hours, the mixture was washed by centrifugation with ethanol for 6 times and freeze-dried for 24 hours to obtain ruthenium-palladium alloy hydride.
[0073] Example 7
[0074] Metal palladium nanodendrites were prepared by referring to Example 1;
[0075] 4 mg of metal palladium nanodendrites were added to 32 mL of 50% ethanol by volume ethanol aqueous solution for dispersion, and then 0.1 mL of 0.05 mol / L copper chloride dihydrate solution and 0.5 mL of 0.5 mol / L 1-naphthol ethanol solution were added. After solvothermal reaction at 200°C for 12 hours, the mixture was washed by centrifugation with ethanol for 6 times and freeze-dried for 24 hours to obtain copper-palladium alloy hydride.
[0076] Example 8
[0077] Metal palladium nanodendrites were prepared by referring to Example 1;
[0078] 4 mg of metal palladium nanodendrites were added to 32 mL of 50% ethanol by volume ethanol aqueous solution for dispersion, and then 0.1 mL of 0.05 mol / L nickel chloride solution and 0.5 mL of 0.5 mol / L 1-naphthol ethanol solution were added. After solvothermal reaction at 200°C for 12 h, the mixture was washed by centrifugation with ethanol for 6 times and freeze-dried for 24 h to obtain nickel-palladium alloy hydride.
[0079] Example 9
[0080] Metal palladium nanodendrites were prepared by referring to Example 1;
[0081] 4 mg of metal palladium nanodendrites were added to 32 mL of ethanol aqueous solution with a volume percentage of 50% ethanol for dispersion, and then 0.1 mL of 0.05 mol / L ferric chloride hexahydrate solution and 0.5 mL of 0.5 mol / L 1-naphthol ethanol solution were added. After solvent thermal reaction at 200°C for 12 hours, the mixture was washed by centrifugation with ethanol for 6 times and freeze-dried for 24 hours to obtain iron-palladium alloy hydride.
[0082] Example 10
[0083] Metal palladium nanodendrites were prepared by referring to Example 1;
[0084] 4 mg of metal palladium nanodendrites were added to 32 mL of 50% ethanol by volume ethanol aqueous solution for dispersion, and then 0.1 mL of 0.05 mol / L zinc chloride solution and 0.5 mL of 0.5 mol / L 1-naphthol ethanol solution were added. After solvothermal reaction at 200°C for 12 h, the mixture was washed by centrifugation with ethanol for 6 times and freeze-dried for 24 h to obtain zinc-palladium alloy hydride.
[0085] Embodiment 11
[0086] Metal palladium nanodendrites were prepared by referring to Example 1;
[0087] 4 mg of metal palladium nanodendrites were added to 32 mL of ethanol aqueous solution with a volume percentage of 50% ethanol for dispersion, and then 0.1 mL of 0.05 mol / L cobalt chloride hexahydrate solution and 0.5 mL of 0.5 mol / L 1-naphthol ethanol solution were added. After solvent thermal reaction at 200°C for 12 hours, the mixture was washed by centrifugation with ethanol for 6 times and freeze-dried for 24 hours to obtain cobalt-palladium alloy hydride.
[0088] Comparative Example 1
[0089] Metal palladium nanodendrites were prepared by referring to Example 1;
[0090] 4 mg of metal palladium nanodendrites were added to 32 mL of benzyl alcohol solution (benzyl alcohol was analytical grade, ≥99%) for dispersion, and then 0.1 mL of 0.05 mol / L ruthenium chloride solution and 0.5 mL of 0.5 mol / L 1-naphthol ethanol solution were added. After solvothermal reaction at 200°C for 12 h, the mixture was washed by centrifugation with ethanol for 6 times and freeze-dried for 24 h to obtain a ruthenium-palladium alloy.
[0091] The ruthenium-palladium alloy hydride described in Example 1 and the ruthenium-palladium alloy described in Comparative Example 1 were subjected to XPS testing. The test results are as follows: Figure 2 As shown by Figure 2 It can be seen that the valence band of the ruthenium-palladium alloy hydride is significantly narrowed, proving the formation of the metal alloy hydride.
[0092] Comparative Example 2
[0093] Metal palladium nanodendrites were prepared by referring to Example 1;
[0094] 4 mg of metal palladium nanodendrites were added to 32 mL of 50% ethanol aqueous solution for dispersion, and then subjected to solvothermal reaction at 200° C. for 12 h, and then washed by centrifugation with ethanol for 6 times, and freeze-dried for 24 h to obtain palladium hydride;
[0095] XRD test was performed on the ruthenium-palladium alloy hydride described in Example 1, the ruthenium-palladium alloy described in Comparative Example 1, and the palladium hydride described in Comparative Example 2. The test results are as follows: Figure 3 As shown by Figure 3 It can be seen that the strongest diffraction peak of ruthenium-palladium alloy hydride shifts to the left compared with the strongest diffraction peak of ruthenium-palladium alloy, which is caused by lattice expansion. At the same time, it shifts to the right compared with the strongest diffraction peak of palladium hydride. The results show the effective synthesis of metal hydrides.
[0096] Application Example 1
[0097] The ruthenium-palladium alloy hydride described in Example 1 and the ruthenium-palladium alloy described in Comparative Example 1 were tested for hydrogen production by electrolysis of water using a standard three-electrode system and a CHI 660E workstation (CH Instruments, Shanghai Chenhua Co., Ltd.) at room temperature. The ruthenium palladium alloy hydride described in Example 1, the ruthenium palladium alloy described in Comparative Example 1, and the palladium hydride of Comparative Example 2 were respectively mixed with conductive carbon powder in a mass ratio of 1:1, and isopropanol, water, and Nafion solution (5wt.%) were added in a volume ratio of 6:3:1 to obtain ink (the concentration of the catalyst for electrolysis of water to produce hydrogen in the ink was 2g / L); 10μL of the ink droplet was added to a glassy carbon electrode (d=3mm), and the glassy carbon electrode was used as the working electrode, the graphite rod was used as the counter electrode, and the saturated calomel reference electrode was used as the reference electrode. The electrolysis of water to produce hydrogen was tested in a 1mol / L potassium hydroxide solution. The electrolysis of water to produce hydrogen reaction (HER) was studied at a scan rate of 5mV / s in a 1.0M KOH solution saturated with N2. All electrode potentials are referenced relative to the reversible hydrogen electrode (RHE). In our electrochemical test system, in 1.0M KOH, E(RHE)=E(SCE)+1.068V.
[0098] Overpotential (η) refers to the part of the actual voltage required to exceed the theoretical voltage in order to achieve a certain current density in an electrocatalytic or photoelectrocatalytic reaction. The overpotential value obtained by LSV measurement is one of the key indicators for evaluating the performance of water electrolysis hydrogen production catalysts. Theoretically, for the hydrogen evolution reaction, the closer the overpotential is to 0V, the better the performance of the water electrolysis hydrogen production catalyst. Usually, in order to facilitate the comparison of the electrocatalytic activity of different materials, we will measure the overpotential at 10mAcm -2 At a current density of , it was converted into reversible hydrogen potential (RHE) for comparison. Figure 4 is the test result of linear sweep voltammetry (LSV), Figure 4 It can be seen that at 10 mA cm -2 The overpotentials of the ruthenium-palladium alloy in Comparative Example 1 and the palladium hydride in Comparative Example 2 are 33 mV and 56 mV, respectively, while the overpotential of the ruthenium-palladium alloy hydride in Example 1 is 25 mV. The results show that the introduction of hydrogen atoms and ruthenium atoms can significantly improve the hydrogen production activity of the ruthenium-palladium alloy hydride in the electrolysis of water.
[0099] Application Example 2
[0100] The ruthenium-palladium alloy hydride described in Example 2, the ruthenium-palladium alloy hydride described in Example 3, the ruthenium-palladium alloy hydride described in Example 4, and the copper-palladium alloy hydride described in Example 7 were tested for electrolysis of water to produce hydrogen: the test process was referred to Application Example 1, and the test results were as follows: Figure 5As shown (the ruthenium-palladium alloy hydride described in Example 2, the ruthenium-palladium alloy hydride described in Example 3, the ruthenium-palladium alloy hydride described in Example 4, and the copper-palladium alloy hydride described in Example 7 at 10 mA·cm -2 The overpotential at is shown in Table 1), Figure 5 As shown in Table 1, by adding 0.1mL 0.05mol / L ruthenium trichloride and performing a solvothermal reaction at 200°C, the catalytic performance of the ruthenium palladium alloy hydride can be significantly improved. In contrast, the overpotential of the copper-palladium alloy hydride of Example 7 at the same current density is significantly higher than that of the ruthenium-palladium alloy hydride. This result shows that in terms of catalytic activity, the ruthenium-palladium alloy hydride has a superior performance compared to the copper-palladium alloy hydride.
[0101] Table 1 The ruthenium-palladium alloy hydride of Example 2, the ruthenium-palladium alloy hydride of Example 3, the ruthenium-palladium alloy hydride of Example 4 and the copper-palladium alloy hydride of Example 7 at 10 mA·cm -2 The overpotential at .
[0102] Example Example 2 Example 3 Example 4 Example 7 Overpotential(mV) 33 46 35 49
[0103] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a catalyst for producing hydrogen by electrolysis of water, characterized in that: The following steps are involved: The ethanol-water dispersion of palladium, the metal precursor dispersion and the ethanol solution of 1-naphthol are mixed to perform a solvothermal reaction to obtain the water electrolysis hydrogen production catalyst; The water electrolysis hydrogen production catalyst is an alloy hydride of metal palladium.
2. The preparation method according to claim 1, characterized in that The palladium in the ethanol-water dispersion of palladium is nano-palladium; The microscopic morphology of the nano-palladium includes one or more of nanoparticles, nanowires, nanotubes, nanodendrites, nanoflowers, nanorods and nanostars; The concentration of the palladium ethanol water dispersion is 50-200 mg / L.
3. The preparation method according to claim 1, characterized in that: The metal precursor in the metal precursor dispersion includes one or more of ruthenium trichloride, cupric chloride dihydrate, ferric chloride hexahydrate, nickel chloride, zinc chloride and cobalt chloride hexahydrate; The concentration of the metal precursor dispersion is 0.01-0.1 mol / L.
4. The preparation method according to claim 1, characterized in that: The concentration of the 1-naphthol ethanol solution is 0.1-1 mol / L.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The dosage ratio of palladium in the ethanol-water dispersion of palladium to the metal precursor dispersion is (1-10) mg: (0.01-1) mL.
6. The preparation method according to claim 5, characterized in that: The volume ratio of the metal precursor dispersion liquid to the 1-naphthol ethanol solution is (0.01-1): (0.3-0.7).
7. The preparation method according to claim 6, characterized in that: The temperature of the solvent thermal reaction is 100 to 240° C., and the time is 1 to 36 hours.
8. The preparation method according to claim 7, characterized in that: After the solvothermal reaction is completed, centrifugal washing and drying are performed in sequence.
9. The catalyst for producing hydrogen from electrolysis of water prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The water electrolysis hydrogen production catalyst is a metal alloy hydride; The metal alloy hydride includes palladium crystals and dopant metal atoms and hydrogen atoms embedded in the palladium crystal structure.
10. Use of the water electrolysis hydrogen production catalyst according to claim 9 in the field of water electrolysis hydrogen production.
Citation Information
Patent Citations
Method for preparing nano-palladium electro-catalyst by ethanol reduction
CN102872861A
Preparation method of alloy hydride material and application thereof
CN108855225A
Pd-Cu alloy icosahedron nano-catalyst as well as preparation method and application thereof
CN114525538A
Preparation method of palladium hydride
CN115872361A
Preparation and application of nano-palladium hydride and palladium-hydrogen-based alloy-state nano-material
CN117069062A